Sports and Recreation Related Concussion - Hazelwood, Vikki (McGraw-Hill's AccessEngineering., 2022)
A sports and recreation related concussion (SRC) is challenging to diagnose. Assessment is clinical and is done using multiple tools, none of which can define a concussion independently or with precise quantitative physiologic measures. As a result, a concussion can easily be missed or presumed resolved. More specific and reliable tools are needed. This case provides clinical background on concussion and describes the extent to which newer technology has been applied to evaluate concussions; it also identifies some opportunities for further development of clinical tools.